Cross-border political ties: foreign firms’ campaign contributions and the crowding out of domestic competitors - Ayyagari, Meghana; Knill, April; Syvrud, Kelsey (Journal of International Business Studies, 2024)
Abstract A substantial body of literature has shown that political connections have benefited firms domestically, but their cross-border value for multinational enterprises (MNEs) remains understudied. This paper provides novel evidence on the strategic advantages MNEs gain through political ties in host countries and the consequences for domestic firms. Examining foreign companies’ contributions to US political campaigns through political action committees (PACs) sponsored by their US subsidiaries, we find that contributing foreign firms win significantly more U.S. government contracts than non-contributing foreign firms. Crucially, this increased access for foreign contributing firms crowds out government contract allocation to similar domestic firms that do not make political donations, even in regulated industries favoring domestic suppliers. Our findings demonstrate that MNEs can effectively leverage political connections as a non-market strategy to gain preferential treatment over local competitors in a host nation. However, these cross-border political ties come at the expense of domestic firms’ competitiveness, informing policy debates around restricting foreign corporate influence in domestic elections. From a managerial perspective, our findings suggest that strategic political ties are an important consideration for MNEs alongside traditional location factors when evaluating foreign investment decisions and navigating institutional complexities abroad.